Wound healing activity of Combination Propolis and Coconut Shell Liquid Smoke Ointment on wistar rat second degree Burns wound models - Aida ayu chandrawati; Marhaen Hardjo; Syahrijuita Kadir (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The delay in burns healing is a serious complication that can lead to disability and death. TGF-?1 contributes significantly to the wound healing process. Chronic wounds that do not heal often indicate a loss of TGF-?1 signaling. Propolis and coconut shell liquid smoke (CS-LS) are natural ingredients that contain antioxidant, anti-inflammatory, and analgesic compounds to accelerate wound healing. This study aimed to prove the effectiveness of using a topical combination of propolis and CS-LS in accelerating the healing process of degree II burns and their relationship with the expression of TGF-?1 in serum. Method: A 14-day in vivo experimental investigation using Wistar rats was carried out with a total sample of 25 rats divided into 4 groups.; Group 1, treated with sulfadiazine ointment; Group 2, treated with propolis ointment; Group 3, treated with CS-LS ointment; Group 4, treated with the combination of propolis and CS-LS ointment, and 1 control group without treatment. Serum TGF-?1 levels were determined by ELISA. Result: Measurements of wound size were on days 0,3,7 and 14. This study obtained results the combination ointment group alone had significantly different TGF-?1 levels from day 7 to day 14 and experienced a decrease in TGF-?1 levels of 52.28 ?/mg. Based on wound size, there was a significant difference in all groups (p<0.05), this was supported by the mean value of wound size which was smaller in the sulfadiazine ointment group and the combination (propolis and liquid smoke) ointment group. Conclusion: The combination of propolis and coconut shell liquid smoke can be considered as an alternative in the treatment of second degree burns because of its ability to reduce TGF-?1 and accelerate burn wound healing. Keywords: wound healing, propolis, coconut shell liquid smoke, TGF-?1